Participatory Approaches in Managing Corporate Social Responsibility (CSR) Funds at Sharia Microfinance Institution - Meranti, Inud Danis Ikhwan; Rosyidi, Laily Hidayati; Masruchi, Zainal Aris (Journal of Islamic Economics and Philanthropy, 2024)
Companies implement CSR programs for a variety of reasons, including social, economic, and legal. As an external entity operating in someone else's territory, companies must pay attention to the welfare of the surrounding community. CSR aims to improve the welfare of society, which includes meeting the material, spiritual, and social needs of citizens so that they can live properly, develop, and function socially. This study uses a descriptive qualitative design with the aim of gaining in-depth insight into the phenomenon under study, namely the management of CSR funds through a participatory approach. participatory increases transparency and accountability in the management of CSR funds. By involving various stakeholders in decision-making, the process becomes more open and can be monitored. In conclusion, this study shows that the participatory approach in managing CSR funds at BMT Al-Yaman Berasan Banyuwangi not only increases the effectiveness of the program, but also provides greater and sustainable social impact for the communities served. Through the distribution of CSR funds to the Pokdarwis of Kawang Pine Beach Wringinputih-Muncar Banyuwangi Regency BMT Al-yaman Berasan Banyuwangi has contributed to the Triple Bottom Lines, namely profit, people and planet, so that BMT Al-yaman Berasan Banyuwangi is included in Micro Finance Institutions that care about the environment and have a good impact on the community that utilizes mangrove products on Kawang Pine Beach to be produced into chips and tea that have been exported to Hong Kong and the Netherlands.